Large Deformation Constitutive Theory for a Two-Phase Shape Memory Alloy - PANOSKALTSIS, Vassilis P.; POLYMENAKOS, Lazaros C.; SOLDATOS, Dimitris (Engineering Transactions, 2014)
In this work we examine significant theoretical issues related to the constitutive modelling of a two-phase shape memory alloy which undergoes large deformations. For this purpose, we propose a new generalized plasticity based model. The model is based on a standard fractions approach and considers a local multiplicative decomposition of the deformation gradient into elastic and inelastic (transformation induced) parts, as its basic kinematic assumption. We also assess the ability of the model in simulating several patterns of the complex behavior of the material in question, by three representative numerical examples. These examples comprise a standard uniaxial tension problem, a torsion problem and an additional problem dealing with non-conventional pseudoelastic response.